ANALISIS PENGARUH CURRENT RATIO (CR) TERHADAP DEBT TO ASSET RATIO (DAR) PADA PERUSAHAAN TRANSPORTASI DAN LOGISTIK YANG TERDAFTAR DI BEI - Anjani, Resti Ratna; Devi, Rizca Puspita (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2025)
The purpose of this study is to understand how liquidity as measured by Current Ratio (CR) and Debt to Assets Ratio (DAR) affects land transportation companies listed on the Indonesia Stock Exchange (IDX). This study uses a quantitative approach with a population that includes 37 companies in the transportation and logistics sector listed on the IDX. For sample selection, purposive sampling method was used so that 10 companies were selected as research subjects. Data analysis was carried out using the simple linear analysis method through SPSS software. The results showed that liquidity (CR) has a partially significant effect on Debt to Assets Ratio (DAR) in transportation and logistics companies listed on the Indonesia Stock Exchange during the period 2020-2023, with a significance level of 0.027 and a t value of 2.024. The relationship found between these two variables is negative. This indicates that the higher the CR value of a company, the lower its DAR value, which indicates that companies with high levels of liquidity tend to have lower dependence on debt